The Untold Story of Training Students with Generative AI: Are We Preparing Students for True Learning or Just Personalization? - Bae, Haesol; Bozkurt, Aras (Online Learning, 2024)
This special issue joins the recent but growing effort to expand understanding of integrating generative AI. While generative AI tools like ChatGPT offer great opportunities for personalized learning, it is important to think critically about what type of learning we are reinforcing through the convenience and customization offered by AI. The reliance on AI for scaffolding and personalized prompts can risk undermining students' independent thinking and problem-solving abilities. Additionally, the emphasis on personalized learning could deter the development of collaboration skills. As we continue to integrate AI into educational practices, we need to work towards balancing the benefits of personalization with the goal of fostering self-reliant, critical thinkers who can collaborate and evaluate AI-generated content.